The Influence of Financial Performance and Economic Performance on the Financial Stability of ASEAN Islamic Banking - Ikrar Syahdani; Sofyan Rizal; Roikhan Mochammad Aziz (LP2M IAIN Palopo, 2026)
Global dynamics and geopolitical uncertainty put pressure on the stability of the financial system, including Islamic banking. Fluctuations in Islamic financial and economic performance tend to be unstable, potentially hampering real sector growth and reducing the competitiveness of the Islamic economy globally. This research uses a quantitative approach with a panel data regression method, which combines time series and cross-sectional data. The variables used include financial performance indicators, namely ROE, ROA, CAR, and NPF, as well as economic performance indicators, including GDP growth, inflation, and the unemployment rate. These findings indicate that certain macroeconomic variables and profitability levels play a role in maintaining the stability of the Islamic banking system. The implications of this research emphasize the importance of incorporating labor market indicators into macroprudential policies, the need for a different approach in handling interbank crises, and the acceleration of digitalization due to the pandemic, which presents both opportunities and risks for financial stability.